SYNTHESIS AND CHARACTERIZATION OF SOME NOVEL 2-[(5-ARYL)-4, 5-DIHYDRO-1H-PYRAZOLE-3-YL]-1H-BENZIMIDAZOLES WITH ANTIMICROBIAL ACTIVITY (International Journal of Pharmaceutical Sciences and Drug Research, 2014)
A novel series of 4-(1H-benzo[d]imidazol-2-yl)-6-phenyl-2-pyrimidinamines (6a-h) have been synthesized in good to excellent yields by using commercially available o-phenylenediamine (o-PDA) (1a-d) and α-hydroxy propionic acid 2 and by involving 2-(α-hydroxy)ethyl benzimidazoles (3a-d), 2-acetyl benzimidiazoles (4a-d) and 1-(1H-benzimidazol-2-yl)-3-(substituted phenyl) prop-2-en-1-ones (5a-h) as intermediates. The chemical structures of the all newly synthesized compounds were clarified by their IR, 1H & 13C NMR, mass spectral data and elemental analysis. Finally, the target compounds were used to find their antimicrobial activity against various microorganisms.